Reconstruction and rehabilitation of short-range gunshot injury to lower part of face: A systematic approach of three cases - Ashutosh Vatsyayan (Chinese Journal of Traumatology, 2016)
Gunshot injuries are always known to cause severe morbidity and mortality when head and neck are involved. They vary in morbidity, which can occur in civilian surroundings. The wound largely depends on the type of weapon, mass and velocity of the bullet, and the distance from where it has been shot. Close-range gunshot wounds in the head and neck region can result in devastating aesthetic and functional impairment. The complexity in facial skeletal anatomy cause multiple medical and surgical challenges to an operating surgeon, demanding elaborate soft and hard tissue reconstruction. Here we presented the successful management of three patients shot by short-range pistol with basic life support measures, wound management, reconstruction and rehabilitation.